Effect of praziquantel on intraocular cysticercosis: a case report. Issue 10 (October 1985) - Kestelyn, P; Taelman, H
Abstract : A patient with intravitreous cysticercosis was treated with the new anthelminthic drug, praziquantel. A transient toxic effect on the cysticerus was observed, but the drug was unable to kill the parasite.